Offshore oil production units: a new concept of oil production floating hull. (4th April 2012) - Jr, Joel Sena Sales; EsperanÁ?a, P. Tarso; Levi, C.; Matos, Vinícius
The Floating, Production, Storage and Offloading (FPSO) production systems have become a popular choice and may produce fairly appropriate technical and economic benefits for oil fields located far away offshore. In such a condition, underwater pipeline networks would not certainly be adequate. An alternative solution would be the use of large capacity floating reservoir to store the processed oil on board and ship it to shore by smaller shuttle tankers. Thus, some desirable features for the FPSO system include large storage capacity, large deck–areas to accommodate separation plant and good hydrodynamic performance when acted by ocean waves, wind and sea currents. Until very recently, there were worldwide offers of old large tankers approaching life cycle limit. Such a market characteristic helped to increase the number of conversion of old large tankers onto stationary floating production units. The declining of that market associated with the fast increasing of the number of FPSO new projects to be installed mostly in the Southeastern Brazilian Coast, the Western Coast of Africa and, more recently due to relaxation in the legislation, in the Gulf of Mexico, has pressed for changes in the way the next generation of FPSO will be planned. It is clear now that most of the new FPSO hulls will need to be designed and built from scrap. On the other hand, the design of a ship–like hull form to work specifically as a stationary unit raises opportunities to improve its operational performance. There is a wide open field for potential innovations to be incorporated into the design of new FPSO hulls to increase their hydrodynamic performance and to achieve higher efficiency and significant savings derived from using less–expensive equipments and possibly increasing operational time. The motivation of this paper is deeply involved in the perspectives mentioned earlier. It discusses results related to a new particular concept for a FPSO hull. The main focus of the discussion points towards the hydrodynamic behaviour of the new hull in waves and tries to identify its potential effects on costs and operational revenue.